A New Look at Campaign Advertising and Political Engagement: Exploring the Effects of Opinion-Congruent and -Incongruent Political Advertisements. (February 2015) - Matthes, Jörg; Marquart, Franziska
Exposure to cross-cutting versus like-minded political advertising is highly relevant in terms of deliberative democratic theory. However, few efforts have been made to shed light on the effects of such opinion-incongruent and -congruent political advertisements. By analyzing data from a representative panel survey, and hence identifying effects over time, we found that exposure to opinion-congruent advertising enhanced political participation. Opinion-congruent advertising also accelerated the timing of voting decisions when citizens were low in ideological strength. However, contrary to our expectations, exposure to opinion-incongruent political advertising had no effects on political participation and the timing of voting decisions. These findings suggest that opinion-congruent advertising is a strong mobilizer, whereas opinion-hostile advertising is a weak cross-pressure. Implications of these findings for the study of political advertising effects are discussed.